The homing pigeons' olfactory map is affected by geographical barriers. Issue 3 (4th May 2021) - Gagliardo, Anna; Pollonara, Enrica; Wikelski, Martin
Abstract : The factors affecting the olfaction-based navigational performances of homing pigeons released at relatively long distance (beyond 100 km from home) have in the past been subject to several investigations both in Germany and Italy using observations of vanishing bearing distributions. These studies highlighted the complexity of long-distance navigation in homing pigeons, which remains a poorly investigated aspect. In this tracking study we report how the homing performances of pigeons housed in Arnino (Pisa, Italy) were affected by the presence/absence of a mountain range (the Northern Apennines) interposed between the home and the release site area (release sites: Trans = mountain barrier, Cis = no mountain barrier). We displaced unmanipulated control pigeons, anosmic pigeon, and pigeons transported in purified air to release sites located at a distance ranging between 95 and 246 km from home. There, birds were released without further manipulation. The navigational performances of anosmic pigeons were impaired at both Cis and Trans sites compared to both smelling groups. Both unmanipulated control pigeons and pigeons transported in purified air but allowed to smell environmental air at both the release site and after release displayed unimpaired navigational abilities at the Cis site, but impaired homing success and impaired homeward orientation at the Trans sites. Nevertheless, their homeward component was significantly greater than that of the anosmic birds at both geographical areas. This suggests that the Northern Apennine acts as a geographical barrier affecting the olfactory map accuracy of Arnino pigeons, rather than totally reducing its spatial extent.